Evaluasi Nilai Fungsional dan Estetika Taman Maccini Sombala Kota Makassar sebagai Taman Hortikultura - YANTI, CRI WAHYUNI BRAHMI; NURFAIDA, NURFAIDA; A KAISAR ALRIAN, A KAISAR ALRIAN (Jurnal Arsitektur Lansekap; Vol.1, No.2, Oktober 2015DO - 10.24843/JAL.2015.v01.i02.p01, 2015)
ABSTRACT Evaluation of Functional and Aesthetic Value of Park Maccini Sombala of Makassar City as Horticultural Parks This study aims to evaluate the functional and aesthetic value of Park Maccini Sombala, Makassar as a horticultural park and make recommendations based on the evaluation. The research phases consisted of an inventory phase, analysis, and synthesis. The inventory phase was conducted to collect data on the physical, biophysical and social. The analysis phase was conducted based on descriptive and qualitative analysis on the data collected and KPI (Key Performance Index) assessment for the physical components, the quality of the park, soft materials, hard materials, as well as visitors. Synthesis phase was carried out to make a recommendation of allocation of the park as park horticulture. Evaluation of the functional and aesthetic value indexes of Park Maccini Sombala as horticultural garden result in KPI total value of all components of 0.70 on a scale of 0 - 1. The proposed recommendations are divided into general recommendations and the specific recommendations. Addition and improvement of soft and hard material condition are given as the general recommendation, whereas specific recommendations is specified for the allocation of the park as horticultural parks, namely the development of the park's horticultural experimental garden, seed, garden education and research, as well as horticultural tourist park.   Keywords : key performance index, functional and aesthetic evaluation, hortikultura park